An Ethnobotanical Survey of Medicinal Plants in Thoranamalai Hill in Thirunelveli, Tamil Nadu, India - Rakulini, S.; Pholtan Rajeev, S.R.; Sounthararajan, K. (University of Sri Jayewardenepura, 2025)
Thoranamalai hill looks like an elephant; hence it is called as Vaarana hill. It was believed that Agathiyar stayed here and did research on medicines. The way from downhill to hilltop is full of greenery. There are herbal plants all along the way to the hill temple. The temple’s specialty being that there are sixty-four natural water springs (Sunai) around the Hill. It is believed that if devotees take bath in these springs will cure their skin diseases. An Ethno-botanical survey was carried out to record information on medicinal plants from Thoranamalai hill. The aim of the study is to identified and documented the Medicinal plants available in the Thoranamalai Hill. Field survey was done, and Medicinal plants were identified with the help of the common public and data was confirmed by traditional practitioners with direct interview conversation. According to this survey, 216 Medicinal Plants were identified and documented. Commonly, These Medicinal plants were belonging to Fabaceae Family. 57% of Shrub taxonomy medicinal plants were recorded. Most of the medicinal plants have medicinal properties. Six rare medicinal plants were identified. Identified Medicinal plants were conservatized and preserved in ornamental areas. Medicinal plants can collect from wild resources and utilized for medicine preparation and get more efficacy to treat the diseases.
Keywords: Thoranamalai Hill; Medicinal plants; Ethno-botany; Traditional medicine